New Pedagogical Challenges in the 21st Century Contributions of Research in Education - Bernad Cavero, Olga; Llevot-Calvet, Núria (IntechOpen, 2018)
The societies of the twenty-first century are subject to social, cultural, political, and economic changes. In this context, the school is asked to educate the future citizens in the present. To respond to this kaleidoscopic reality, the school is immersed in a pedagogical revolution. In this book, the reader will find a selection of avant-garde research works from different disciplines and contexts, which have their epicenter in the school and in the faculties of education. New issues in pedagogy and education, and new roles of teachers and students, are discussed in a global and diverse context. And new methodological and formative proposals are also proposed to build the ideal school and the ideal teacher, from the initial and continuous teacher training.